Propuesta de creación de un plan de negocios para el microemprendimiento social y solidario en el sistema de producción de hortalizas agroecológicas - Zavala Salvatierra, Sandry Steward (2022)
This document deals with information regarding a proposal to create a business plan for social and supportive microenterprise in the agroecological vegetable production system. Microentrepreneurship is a set of activities aimed at starting a new business, investing certain resources in a given period and by a work team, or a single person. When it comes to entrepreneurship, innovation plays an important role in gaining competitiveness, especially for organic vegetables, which is what is currently on the rise, to help microentrepreneurs. The conclusions determine that the elaboration of a business plan serves to project the profitability of investing in a new product that is pleasing to the consumer, starting commercial activities, it is of great advantage to carry it out in large cities, for having a market that is continues to expand in the consumption of healthy and nutritious food, it is necessary to promote business development at the rural level, motivating the business initiatives that arise. Peasants and producers need to associate to create a company that allows them to invest, innovate, produce, compete, in order to improve the quality of life of the population and the peasant family. Organic vegetables must be produced as a product that is palatable to the consumer. such as preserves, pickles, fresh with longer preservation time and the benefit of micro-enterprises is that they socially generate the capacity for people to obtain their added value from production, improve economic income, allow them to associate with each other and also help preserve the health of consumers.